On the determinants of long-run inflation uncertainty: evidence from a panel of 17 developed economies - Conrad, Christian; Hartmann, Matthias (European journal of political economy, 2019)
Based on a cross section of 17 advanced economies and data for the period 1975 to 2015, we examine how the interaction between monetary policy and macroeconomic conditions affects inflation uncertainty in the long-term. We construct a proxy for the unobservable inflation uncertainty based on the slowly evolving long-term variance component of inflation from a Spline-GARCH model (Engle and Rangel, 2008). We show that long-run inflation uncertainty is high if an inflation-tolerant central bank governor is in power during a period of high inflation, if the policy rate is below the one that is prescribed by the Taylor rule and during times of heightened stock and exchange rate volatility.
Available online 19 September 2018
Gesehen am 17.04.2019